Bagaimana Generasi Milenial Mendidikan Diri Mereka Sendiri?: Kajian Harmeneutik Terhadap QS. An-Nahl ayat 70 dan Teori Calljum: - Erlina Farah Agustina; Nasikhin Nasikhin; Mustopa Mustopa (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to examine the meaning of QS. Specifically, it will examine An-Nahl verse 70 in the context of the self-education of the millennial generation, using a hermeneutic approach and integrating Calljum's theory. A qualitative method with a library research approach was used to analyze QS. The verse is analyzed and related to Calljum's theory in the context of millennial generation self-education. Through hermeneutic analysis, the verse is understood not only textually but also in relation to the phenomenon of "digital senility," in which technology can erode spiritual values. Integrating Calljum's theory results in a holistic self-education model emphasizing critical literacy and collaborative learning. The implementation strategy includes using technology for divinatory learning and strengthening soft skills. The study concludes that self-education for millennials must be adaptive and reflective, as well as oriented toward balanced character building that considers both the intellectual and the spiritual.